Brain drawings following traumatic brain injury (TBI) and links to illness perceptions and health outcomes – Findings from a population-based study. Issue 10 (2nd October 2016) - Jones, Kelly M.; Kydd, Rob; Broadbent, Elizabeth; Theadom, Alice; Barker-Collo, Suzanne; Edwards, Holly; Feigin, Valery L.; ,
Abstract : Objective : Individuals' illness perceptions predict health behaviours and influence functional outcomes. This study examined associations between a novel assessment of illness perceptions, in the form of adult's brain drawings after traumatic brain injury (TBI) and questionnaire measures of illness perceptions, quality of life and post-concussive symptoms. Design : Population-based, prospective longitudinal study examining 245 adults with predominantly mild TBI with high risk of complications. Main outcome measures : Participants were asked to draw pictures of what they thought their brain looked like before injury and at baseline and one month post-injury. Drawing characteristics (height, width and percentage damage at one month) were examined in relation to each outcome of interest at six months. Results : Greater damage at one month was associated with more negative illness perceptions ( r s = .23), poorer mental health ( r s = −.21), and more total post-concussive symptoms ( r s = .27 to r = .35) at six months. The extent of damage depicted reduced over time ( p < .001). No associations were found between the amount of damage drawn and injury severity, nor the height or width of drawings and injury severity or illness perceptions. Conclusion : Drawings post-TBI offer a simple, cost- and time-effective way to begin discussions and improve understanding of peoples' illness perceptions.